Unexpected complexity of the Wnt gene family in a sea anemone - Kusserow, Arne; Holstein, Thomas W. (Nature, 2005)
The Wnt gene family encodes secreted signalling molecules that control cell fate in animal development and human diseases. Despite its significance, the evolution of this metazoan-specific protein family is unclear. In vertebrates, twelve Wnt subfamilies were defined, of which only six have counterparts in Ecdysozoa (for example, Drosophila and Caenorhabditis). Here, we report the isolation of twelve Wnt genes from the sea anemone Nematostella vectensis , a species representing the basal group within cnidarians. Cnidarians are diploblastic animals and the sister-group to bilaterian metazoans. Phylogenetic analyses of N. vectensis Wnt genes reveal a thus far unpredicted ancestral diversity within the Wnt family. Cnidarians and bilaterians have at least eleven of the twelve known Wnt gene subfamilies in common; five subfamilies appear to be lost in the protostome lineage. Expression patterns of Wnt genes during N. vectensis embryogenesis indicate distinct roles of Wnts in gastrulation, resulting in serial overlapping expression domains along the primary axis of the planula larva. This unexpectedly complex inventory of Wnt family signalling factors evolved in early multi-cellular animals about 650 million years (Myr) ago, predating the Cambrian explosion by at least 100 Myr (refs 5, 8). It emphasizes the crucial function of Wnt genes in the diversification of eumetazoan body plans.